Voltage flicker estimation based on pair of inter-harmonics analysis method - Mohd Radzi, Mohd Amran; Goh, Zai Peng; Hizam, Hashim (Universiti Putra Malaysia Press, 2017)
This paper presents a voltage flicker estimation based on a pair of inter-harmonics analysis method. The proposed algorithm is able to estimate flicker frequency and amplitude changes of a voltage waveform. The correlation of the pair of inter-harmonics, flicker frequency, and amplitude changes are presented and their formulas highlighted. Experimental results indicate the amplitude of pair of inter-harmonics can detect the voltage flicker. Furthermore, the experimental results are compared with the measurement results obtained by using the Fluke power analyzer (Pst).